(Un)acceptability of the clitic pronoun placement pattern in Brazilian Portuguese by educated speakers - Pereira, Ronan (2023)
Brazilian Portuguese prioritizes pre-verbal placement (proclisis) of its clitic pronouns. However, post-verbal placement (enclisis) has not been completely excluded from this variety, being acquired by means of schooling. This study aimed at evaluating the acceptability of both these possible clitic placements in sentences with and without proclisis triggers – elements that, according to the normative tradition (based on European Portuguese, whose clitic placement pattern is syntacticly restrained), give rise to proclisis (whereas enclisis obtains at their absence) – by means of an acceptability judgement test with a six-point scale carried out by 79 Brazilian Portuguese native speakers who had completed, at least, Secondary School. The results showed that, even though the items with proclisis have been better evaluated than the ones with enclisis, the enclitic placement was evaluated above the central point of the scale used in this study, indicating that it is, as well, an acceptable placement for those speakers. It is concluded that, although the classes regarding clitic placement revolve around teaching the students similar rules to those found in the European Portuguese syntax, it does not seem to allow them to develop the syntactic knowledge specific to proclisis and enclisis, probably because Brazilian Portuguese is the oral variety used in the classrooms and the clitic placement rules (and their application) are restricted to the written modality.